The Abortion Platformization in the United States: A Critical Perspective - Tamara Roma (Labour & Law Issues)
The article delves into the topic of digital abortion in the United States, focusing on how the possibility of obtaining an abortion through mifepristone has transitioned into the digital realm and how the law might support, reinforce, challenge, or be challenged by gender dynamics. With these objectives, first, the contribution traces the historical and legal evolution that drove the abortion platformization – in other words, the digitalization of abortion services via online platforms – highlighting how this evolution led to the structuring of a digital abortion ecosystem. In a second moment, the challenges faced by this digital abortion ecosystem during the Roe era – when abortion was still recognized as a constitutional right – are underlined. Finally, the contribution moves to analyze the consequences for this ecosystem’s users and workers of the Supreme Court ruling Dobbs v. Jackson, which overturned Roe v. Wade returning abortion regulation to the states.